Oscillation detection of a quadrotor system carrying suspended payload using image processing technique - Ramli, Liyana; Mohd Awi, Amalin Aisya; M. Lazim, Izzuddin; Mohamed, Zaharuddin; Jaafar, Hazriq Izzuan (Penerbit Universiti Malaysia Terengganu, 2022)
This paper proposes using an image processing technique to detect the oscillation deflection of a quadrotor system carrying a suspended payload. A wireless smart camera is attached underneath the quadrotor to capture the payload oscillation in transit from one place to another. The image processing technique was used to measure the oscillation and response based on the output signal captured by the smart camera. A Parrot BEPOP quadrotor drone was used for the experiment and the image processing technique was realised using MATLAB software. Experiments were carried out to detect and analyse the payload oscillation response under different payload masses. The experiment results demonstrate the effectiveness of the image processing technique in detecting the payload oscillation under different payload masses.